Settler aesthetics : visualizing the spectacle of originary moments in The new world - Goeman, Mishuana (University of Nebraska Press, 2023)
"In Settler Aesthetics, an analysis of renowned director Terrence Malick's 2005 film, The New World, Mishuana Goeman examines the continuity of imperialist exceptionalism and settler-colonial aesthetics. The story of Pocahontas has thrived for centuries as a cover for settler-colonial erasure, destruction, and violence against Native peoples, and Native women in particular. Since the romanticized story of the encounter and relationship between Pocahontas and Captain John Smith was first published, it has imprinted a whitewashed historical memory into the minds of Americans. As one of the most enduring tropes of imperialist nostalgia in world history, Renaissance European invasions of Indigenous lands by settlers trades in a falsified "civilizational discourse" that has been a focus in literature for centuries and in films since their inception. Ironically, Malick himself was a symbol of the New Hollywood in his early career, but with The New World he created a film that serves as a buttress for racial capitalism in the Americas. Focusing on settler structures, the setup of regimes of power, sexual violence and the gendering of colonialism, and the sustainability of colonialism and empires, Goeman masterfully peels away the visual layers of settler logics in The New World, creating a language in Native American and Indigenous studies for interpreting visual media"-- Provided by publisher.
Keywords: Pocahontas, -- -1617 -- In motion pictures.; Malick, Terrence, -- 1943- -- Criticism and interpretation.; New world (Motion picture); Malick, Terrence, -- 1943-; Pocahontas, -- -1617; Historical films -- History and criticism.; Settler colonialism.; Indians of North America -- First contact with other peoples.; Indians in motion pictures.; Films historiques -- Histoire et critique.; Colonialisme de peuplement.; Peuples autochtones -- Premiers contacts avec d'autres peuples -- Amérique du Nord.; Peuples autochtones au cinéma.; SOCIAL SCIENCE / Media Studies.; SOCIAL SCIENCE / Ethnic Studies / American / Native American Studies.; Historical films; Indians in motion pictures; Indians of North America -- First contact with other peoples; Motion pictures; Settler colonialism; Electronic books.; Criticism, interpretation, etc.; Film criticism; Film criticism.; Critiques cinématographiques.